Microbial valorization of oil-based substrates for polyhydroxyalkanoates (PHA) production – Current strategies, status, and perspectives - Lim, Sook Wei; Jibrail Kansedo; Tan, Inn Shi; Tan, Yie Hua; Jobrun Nandong; Lam, Man Kee; Clarence M. Ongkudon (Elsevier, 2023)
With the rising interest in developing polyhydroxyalkanoate (PHA) bioplastics as an auspicious substitute for conventional plastics, the exploitation of low-cost oil substrates for PHA biosynthesis has become popular recently. In view of the paucity of feasibility studies on lipid-based PHA production, this paper aims to provide an overview of the PHA production from diverse lipid-rich sources, covering the PHA production efficiencies using different plausible fermentation strategies and the key influencing factors for oil-based PHA production. Considering the high conversion efficiency (97.5% of the theoretical PHA yield), direct fermentation of oil has shown great promise for PHA industrialization. Plant oils which could achieve a high PHA yield (0.25–0.77 g/g) are better carbon sources than waste cooking oil (0.15–0.28 g/g). In addition to providing information on the potential enhancement tools (i.e., mixed cultures, metabolic engineering, and kinetic studies) for lipid-based PHA production, this paper also reviews the techno-economic and life cycle assessment of PHA production in comparison to the conventional plastics. Besides, technical challenges and future perspectives for the commercialization of oil-based PHA production have been discussed (specifically targeting on the concerns of inconsistent production efficiency, complex recovery process, and high production cost), offering further insights towards developing a sustainable circular economy.